INOVASI PELAYANAN KTP DIGITAL MELALUI APLIKASI IDENTITAS KEPENDUDUKAN DIGITAL DI KABUPATEN BOJONEGORO - Laila Oktaviani; Esa Septian; Junadi Junadi (Universitas Bina Taruna Gorontalo, 2024)
ABSTRACT The purpose of this study is to determine the extent of the implementation of public service innovation through the IKD application provided by the government together with the Population and Civil Registration Office. The research method used is qualitative descriptive with a case study type approach. Primary and secondary data collection from interviews, observations, documentation are then analyzed and conclusions are drawn from the research problem. The results of this study show that the implementation of Digital KTP innovation has so far been carried out as directed, with the application in making population identity, which is easy, fast does not need to wait long, practical, data is safer and can save the budget for the KTP-el stamp, but in its implementation there are still various problems, namely on the internet network, the application often errors, the device does not support and low public awareness